Epigenetic priming improves salvage chemotherapy in diffuse large B-cell lymphoma via endogenous retrovirus-induced cGAS-STING activation - Jun Liu; Suji Min; Dongchan Kim; Jihyun Park; Eunchae Park; Youngil Koh; Dong-Yeop Shin; Tae Kon Kim; Ja Min Byun; Sung-Soo Yoon; Junshik Hong (Clinical Epigenetics, 2023)
Abstract Background Although most patients with diffuse large B-cell lymphoma (DLBCL) achieve complete remission after first-line rituximab-containing immunochemotherapy, up to 40% of patients relapse and require salvage therapy. Among those patients, a substantial proportion remain refractory to salvage therapy due to insufficient efficacy or intolerance of toxicities. A hypomethylating agent, 5-azacytidine, showed a chemosensitizing effect when primed before chemotherapy in lymphoma cell lines and newly diagnosed DLBCL patients. However, its potential to improve outcomes of salvage chemotherapy in DLBCL has not been investigated. Results In this study, we demonstrated the mechanism of 5-azacytidine priming as a chemosensitizer in a platinum-based salvage regimen. This chemosensitizing effect was associated with endogenous retrovirus (ERV)-induced viral mimicry responses via the cGAS-STING axis. We found deficiency of cGAS impaired the chemosensitizing effect of 5-azacytidine. Furthermore, combining vitamin C and 5-azacytidine to synergistically activate STING could be a potential remedy for insufficient priming induced by 5-azacytidine alone. Conclusions Taken together, the chemosensitizing effect of 5-azacytidine could be exploited to overcome the limitations of the current platinum-containing salvage chemotherapy in DLBCL and the status of cGAS-STING has the potential to predict the efficacy of 5-azacytidine priming.